Profile of global professional breakers qualifying for the Olympic Games: Identifying training patterns, mental health, and injury characteristics - Lindner, S. M.; Schott, N.; Morales-Castillo, S.; Nonnenmann, J.; Steinberg, C. (Journal of Dance Medicine & Science, 2026)
Introduction: Breaking has been included in the 2024 Olympic Games; however, research on the training and injuries of professional breakers remains limited. This study examines the profiles of competitive breakers within national squads worldwide, focusing on the defining characteristics of professional breakers qualifying for the 2024 Paris Olympics regarding their training patterns, mental health, and injury characteristics.